PENGARUH SERVICE QUALITY PRE-EKSPERIMENTAL DAN POST-EKSPERIMENTAL TERHADAP CUSTOMER SATISFACTION DAN CUSTOMER LOYALTY PADA AIC MEDICAL CLINIC - Antoni, Irene; Budianto, Bernard; Ardi, Ardi (NUSANTARA : Jurnal Ilmu Pengetahuan Sosial, 2022)
This study aims to examine the effect of service quality dimensions (reliability, tangibility, responsiveness, assurance, and empathy) on patient satisfaction and its impact on patient loyalty at AIC Medical Clinic. The sample of this study were medical check-up patients who received services at AIC Medical Clinic. The research sample was divided into 2 groups because of the intervention to be studied. The number of research samples before the intervention was 159 respondents, while the number of respondents after the intervention was 193 respondents.This study uses a quantitative approach. The research data obtained from the results of filling out the questionnaire were analyzed using descriptive analysis techniques and SEM PLS analysis techniques. The descriptive analysis was carried out with the help of the SPSS program, while the PLS analysis was carried out using the SmartPLS version 3.2 program.Based on the results of the analysis in this study, it was concluded that partially, reliability, tangibility, responsiveness, assurance and empathy had a positive effect on patient satisfaction, the five dimensions of service quality were also proven to have a significant effect on patient loyalty, while patient satisfaction itself was also proven to have an impact on patient loyalty. The result also found a significant effect of intervention in post-experimental subjects.Â  Overall it is concluded that the better the quality of services provided by AIC Medical Clinic in terms of tangibility, responsiveness, assurance, and empathy, the higher the patient satisfaction which in turn will increase patient loyalty.